Fire Resistance Properties of Palm Oil Fuel Ash Cement Based Aerated Concrete - Khairunisa, Muthusamy; Mohd Warid, Hussin (ISSR, 2010)
POFA cement based aerated concrete, an agro based lightweight concrete containing palm oil fuel ash (POFA) as partial cement substitute; possess adequate strength suitable for non load-bearing element application. This paper discusses fire resistance properties of this material in the aspect of its combustibility, contribution towards fire and its tendency to spread flame over its surface that has been investigated in accordance to BS 476 : Part 4, Part 6. and Part 7 respectively. The findings indicate that the integration of POFA does not affect this agro based material to exhibit good fire resistance.